DYNAMICS OF ANTIBACTERIAL DRUG RESIDUES IN POULTRY MEAT AND EGGS - N.I, Navruzov (Research Focus International Scientific Journal, 2026)
This article examines the distribution of antibacterial drugs in the organism of poultry, their metabolism, and the dynamics of their residual levels in meat and egg products. Antibacterial drugs play an important role in protecting poultry from bacterial diseases. However, their improper or excessive use may negatively affect food safety. The article also analyzes the factors contributing to the formation of antibiotic residues and the methods used for their control.